Assessment strategies for online learning : engagement and authenticity - Conrad, Dianne, 1948-; Openo, Jason (Issues in distance education series., 2018)
"For many learners, assessment conjures up visions of red pens scrawling percentages in the top right-hand corner of exams and feelings of stress, inadequacy, and failure. Although learners sometimes respond negatively to evaluation, assessments have provided educational institutions with important information about learning outcomes and the quality of education for many decades. But how accurate are these data and have they informed practice or been fully incorporated into the learning cycle? Conrad and Openo argue that the potential inherent in online learning environments to alter and improve assessment and evaluation has yet to be explored by educators and learners. In their investigation of assessment methods and learning approaches, Conrad and Openo explore assessment that engages and authentically evaluates learning. They insist that online and distance learning environments afford educators new opportunities to embrace only the most effective face-to-face assessment methods and to realize the potential of engaged learning in the digital age. In this volume, practitioners will find not only an indispensable introduction to new forms of assessment but also a number of best practices as described by experienced educators"--